Pendampingan Pembuatan Website Perusahaan Kenongo Organizer sebagai Program Digital Marketing - M Thoriqul Huda; Nabila, Nabila Mighna Faiza; Nur, Nur laili zakiyah ahmad; Ahmad, Ahmad muflihus syauqi; Wahyu, M.Khabib Wahyu P; Rois, Roisul Musbikhin; Fahrul, Ahmad Fahrul Muzaki (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
A wedding organizer is a CV service provider who personally assists with weddings, planning and predetermined budgets. Problems that occur when potential customers want to find out information or order wedding organizer services while the owner is not there, causing potential customers to have to go back and forth to the wedding organizer and it takes quite a lot of time. The aim of creating this website is not only to promote services but also to help with the transaction process, this website can accommodate online orders for wedding organizing services. In this mentoring activity, the method used is the PAR (Participatory Action Research) method. The PAR (Participatory Action Research) method is a method that combines continuous action by involving several members of the wedding organizer. By providing this assistance, participants are expected to be able to understand the features and use of the website. Technological developments are very influential in increasingly advanced promotional media, so that businesses can run effectively.